1974
DOI: 10.1073/pnas.71.3.894
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nucleolar and Mitochondrial DNA Replication in Tetrahymena pyriformis

Abstract: Selective induction of replication of nucleolar and mitochondrial DNA has been demonstrated in starved-refed cultures of Tetrahymena pyriformis by different techniques.Labeling of starved cells with [3Hithymidine during a nutritional shift-up and analysis of the DNA in isopycnic CsCJ gradients shows that the two initially labeled species of DNA are two species banding on the heavy and light side of the bulk macronuclear DNA. In isolated macronuclei the radioactivity is found only in the high density fraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Our results clearly indicate that the preferential digestion by DNase I of DNA which has been labeled during refeeding of starved Tetrahymena is similar in intact nuclei, isolated nuclesomes and purified nucleosome cores. It has been demonstrated that this defined starvation-refeeding scheme preferentially labels the ribosomal genes (10,11,29,42; see Fig. 1).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our results clearly indicate that the preferential digestion by DNase I of DNA which has been labeled during refeeding of starved Tetrahymena is similar in intact nuclei, isolated nuclesomes and purified nucleosome cores. It has been demonstrated that this defined starvation-refeeding scheme preferentially labels the ribosomal genes (10,11,29,42; see Fig. 1).…”
Section: Discussionmentioning
confidence: 87%
“…Tetrahymena ribosomal genes (rDNA) can be preferentially labeled utilizing a defined starvation-refeeding scheme modified slightly from that originally developed by Engberg et al (42). This procedure yields nuclei in which the bulk DNA has been labeled with 14C-thymidine during exponential growth while rDNA is preferentially labeled with 3H-thymidine during a 2-hour refeeding period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ciliates, satellite DNA has been found in some strains of P. aurelia (Soldo & Godoy, 1972) and in T. pyriformis strain GL (Sueoka, 1961). Gall (1974) and Engberg et al (1974) have shown that macronuclear satellite DNA of T. pyriformis GL corresponds to ribosomal cistrons. In another strain, T. pyriformis WH-6, no detectable satellites were found by Yao & Gorovsky (1974) and no marked differences between micro-and macronuclear DNA base composition was observed.…”
Section: Discussion (I) Gc Contentmentioning
confidence: 99%
“…]5 -0.58M sucrose gradient gives three peaks of RNA, the (irst containing 25 S ribas~ma~ RNA, the second 17 S ribosomal RNA and the third a mixture of 5 S ribosomal RNA, tRNA and mRNA. The genes which code for the two large ribosomal RNAs (25S and 17S) are located in the nucleoli (18) and are often referred to as ribosomal genes. These genes replicate autonomously (2), The 5 S RNA genes are not nucleolar and replicate with the bulk DNA (55), In Tetrahymena tRNAs have sedimentation constants around 4 S and they are not separable form 5 S ribosomal RNA by the method here used.…”
Section: Rnamentioning
confidence: 99%